2011
DOI: 10.1532/hsf98.20111029
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical and Economic Evaluation of Fast-Track Recovery after Cardiac Surgery

Abstract: Fast-track recovery after cardiac surgery decreases the intensive care LOS and the total duration of intubation. It is a cost-effective strategy compared with conventional recovery protocols; however, it does not reduce the total hospital LOS or the incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 19 publications
1
26
0
2
Order By: Relevance
“…For low-risk cardiac surgical patients, transfer of these patients after surgery to a fast-track unit (19)(20)(21) instead of the ICU is safe and can increase throughput by 15% (20), increase ICU bed utilization (20), and is associated with an 8% reduction in perioperative care costs (21). Constantinides et al suggested that the application of the FTF risk model may facilitate planning and now of cardiac surgery, limit FTF rates and help reduce morbidity and cost (8).…”
Section: Discussionmentioning
confidence: 99%
“…For low-risk cardiac surgical patients, transfer of these patients after surgery to a fast-track unit (19)(20)(21) instead of the ICU is safe and can increase throughput by 15% (20), increase ICU bed utilization (20), and is associated with an 8% reduction in perioperative care costs (21). Constantinides et al suggested that the application of the FTF risk model may facilitate planning and now of cardiac surgery, limit FTF rates and help reduce morbidity and cost (8).…”
Section: Discussionmentioning
confidence: 99%
“…Besonders effizient ist die Frühmobilisation bei Einbettung in "Fast-Tracking"-Konzepte [7], die bereits für eine Vielzahl von operativen Prozeduren vorgestellt wurden. Sie ermöglichen den optimierten und somit schnelleren Durchlauf durch den gesamten perioperativen Prozess [93]. Neben dem bereits flächendeckenden Einsatz im ambulanten Bereich [106] könnten solche Fast-Track-Konzepte aber auch bei Hochrisikopatienten das perioperative Risiko vermindern [63].…”
Section: Pulmonale Komplikationunclassified
“…While enhanced recovery was initially developed for colorectal surgery, it has now been evaluated or adopted in a number of other surgeries, including radical cystectomy, hepatobiliary and pancreatic surgery, total knee replacement and cardiovascular surgery. [3][4][5][6][7] The management of an elderly patient undergoing surgery is an evolving challenge. In 2010, 524 million people were above the age of 65 years -8 percent of the world's population.…”
Section: Introductionmentioning
confidence: 99%